Indirect Organogenesis from in vitro Derived Leaf and Internodes of Coccinia cordifolia (L.) Cogn. - An Important Medicinal Climber - Rahman Sarkar, Md Taufiqur; Alam, Mohammad Firoz (Plant Tissue Culture and Biotechnology, 2022)
An efficient in vitro regeneration protocol was developed via callus from the explants of leaf and internode of Coccinia cordifolia (L.) Cogn., an important medicinal climber. Among the different combinations of auxins and cytokines used, BAP with NAA were found highly effective for induction of callus from in vitro derived leaf disc and internode explants. Maximum callus formation rates were recorded on MS with 1.0 mg/l BAP and 0.1 mg/l NAA for both leaf disc and internode explants. The best organogenesis via callus was obtained on MS with 2.0 mg/l BAP and 0.5 mg/l NAA. The highest numbers of shoots regenerated per culture were 6.5 ± 0.10 and 5.6 ± 0.55 for leaf disc and internode explants respectively and leaf discs was found to be better for indirect organogenesis. For root induction, half strength of MS medium supplemented with 0.1 mg/l IBA was found to be the most effective. The mean number of roots regenerated per shoot was 6.8 ± 0.10 with an average root length of 2.8 ± 0.20 cm. In vitro derived plantlets were acclimatized successfully. This protocol for in vitro regeneration can be utilized for the improvement of this climber through biotechnological methods. Plant Tissue Cult. & Biotech. 32(2): 127-136, 2022 (December)